Women, Violence and Work: Threat of Sexual Violence and Women's Decision to Work - Tanika Chakraborty; Nafisa Lohawala (Institute of Labor Economics (IZA), 2021)
The stagnancy of women's workforce participation in urban India is alarming and puzzling, considering the pace of economic development experienced in the previous decade. We investigate the extent to which the low workforce participation of women can be explained by growing instances of officially reported crimes against women. We employ a fixed effects strategy using district-level panel data between 2004-2012. To address additional concerns of endogeneity, we exploit state-level regulations in alcohol sale and consumption and provide estimates from two different strategies – an instrumental variable approach and a border-analysis. Our findings indicate that a one standard deviation increase in sexual crimes per 1000 women reduces the probability that a woman is employed outside her home by 9.4%. While we find some evidence of heterogeneity across regions and religions, overall, the deterrent effect seems to affect women equally across all economic, demographic and social groups.
Keywords: E24; J08; J16; J18; 330; crime-against-women; female labor supply; instrumental variable; alcohol regulation